Dyspepsia in African-American and Hispanic patients. - Akhtar, Abbasi J. (National Medical Association, 2004)
Dyspepsia is a common disorder with a prevalence of up to 40% in the general population. The presence of alarm features (age >50 years, loss of appetite, early satiety, loss of weight, dysphagia, abdominal mass, gastrointestinal bleeding, and/or anemia) increase the likelihood of an organic etiology. Despite a plethora of information written on this subject, the literature is sparse in minority populations. We studied the etiology of dyspepsia in relation to age and the presence or absence of alarm features in 678 African-American and Hispanic patients. Five-hundred-thirty patients were investigated by upper gastrointestinal (UGI) endoscopy, 88 by barium radiographs of the UGI tract, and 60 patients had both endoscopy and barium studies. The most common alarm feature in our study was age >50 years, followed by anemia, weight loss, gastrointestinal bleeding, loss of appetite, early satiety, abdominal mass, and dysphagia. The presence of alarm features and older age increased the likelihood of finding an organic lesion. It is concluded, therefore, that endoscopy in our dyspeptic patients who had alarm features appears to increase the diagnostic yield and may consequently result in a more favorable therapeutic outcome.